Protestantizem in deliberacija - Andrejč, Gorazd (Slavia Centralis, 2020)
Protestantism and DeliberationDeliberation as critical, open, inclusive and argument-based discussion about matters of public interest is a crucial mechanism of a healthy democracy. According to deliberative democracy defenders, like Jürgen Habermas, deliberation contributes to achieving a better and more just society. The present essay analyses the intertwinement between the development of this political value in the Euro-Atlantic world on the one hand, and Protestantism and its development on the other. Recent works in the history of Protestantism and the political history of democracy paint a complex, but powerful picture: despite the religious conservative tendencies in Protestantism, it seems that a notable measure of freedom of research, belief and debate could be found in the societies where Protestantism had become a dominant religious culture. While this development is partly a result of contingent historicevents, it also had much to do with internal theological impulses within the Protestant thought.
Keywords: deliberation; Protestantism; democracy; debate; public discussion